INTERPRETATION OF DIFFERENT TYPES OF TUNDRA FROM AERIAL PHOTOGRAPHS AND THEIR AEROVISUAL DESCRIPTION ON THE BASIS OF FROST JOINTING - Andreev,V. N. (1969)
Frost fissuring of the ground surface exerts a considerable influence on the development of vegetation in three groups of plant associations in the tundra zone: (a) in the group of associations of polygonal swamps developing in areas recently emerging from beneath the level of sea, lake or river water; (b) in the group of peaty tundras and tundra peat bogs associated with the interfluves and (c) in the group of arctic deserts and various lichen tundras developing on mineral ground. In each group the frost fissuring has its distinguishing characteristics which create a singular surface pattern. The latter can be successfully used in the interpretation of each group of associations on aerial photographs and for their description by aerovisual observations. Polygonal swamps, under the influence of development of frost fissuring, peat accumulation and melting of permafrost, undergo several stages of development (arctic, ridged, ridged-lake, hummocky-meadow and ridged-polygonal-meadow swamps), each of which has its distinguishing characteristics, created as a result of development of the frost fissure network. The defined types can be distinguished by aerial methods on the basis of these peculiarities. In peaty and tundra peat bogs, under the influence of frost fissuring, processes of drawing out and decomposition of peat occur. As a result, the plant associations and microrelief forms change, affording the possibility for interpreting individual types. (Author) Trans. of Geofizicheskii Sbornik (USSR) v7 p103-120 1955.